Even more mathematical activities - Bolt, Brian (Cambridge : New York : Cambridge University Press, 1996)
This book contains 133 puzzles, investigations, games, projects and applications of mathematics, together with a commentary which provides solutions and additional ideas.
Includes bibliography references and index.
Keywords: Mathematical recreations